1997
DOI: 10.1093/nar/25.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type specific DNA-protein interactions at the tissue-type plasminogen activator promoter in human endothelial and HeLa cells in vivo and in vitro

Abstract: Tissue-type plasminogen activator (t-PA) gene expression in human endothelial cells and HeLa cells is stimulated by the protein kinase C activator phorbol 12-myristate 13-acetate (PMA) at the level of transcription. To study the mechanism of transcriptional regulation, we have characterized a segment of the t-PA gene extending from -135 to +100 by in vivo footprinting analysis [dimethyl sulphate (DMS) method] and gel mobility shift assay. In vivo footprinting analysis revealed changes in cleavage pattern in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 32 publications
(40 reference statements)
2
55
0
Order By: Relevance
“…The majority of genes selectively up-regulated in CSML100 cells, i.e., the tPA, TIMP-1, mts1, MMP-9, PAI-1, MMP-3, uPAR, and uPA genes, have been reported to be AP-1 dependent under appropriate conditions (5,18,32,33,43,45,54,59). Therefore, it was of interest to examine AP-1 in this cell system.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of genes selectively up-regulated in CSML100 cells, i.e., the tPA, TIMP-1, mts1, MMP-9, PAI-1, MMP-3, uPAR, and uPA genes, have been reported to be AP-1 dependent under appropriate conditions (5,18,32,33,43,45,54,59). Therefore, it was of interest to examine AP-1 in this cell system.…”
Section: Resultsmentioning
confidence: 99%
“…HPV 18 harbors two functional AP-1 binding sites within its URR (Garcia-Carranca et al, 1988), both equally contributing to the ®nal transcription level initiated at the P 105 promoter (Thierry et al, 1992). For EMSA analyses, we selected the distal AP-1 element at nucleotide position 7596 ± 7620 (5'-CGCACCTGGTATTAGT-CATTTTCC-3', Butz and Hoppe-Seyler, 1993), since it is located within the constitutive enhancer region, conferring not only tissue speci®city (Oord and Beard, 1990) but also inducibility to phorbol esters (Gius and Laimins, 1989), known to potentiate the eects of carcinogens and AP-1 activity (Arts et al, 1997). Control experiments using a AP-1 consensus sequence (5'-CGC TT GATGACTCAG CCG GA A -3', Lee et al, 1987) in comparison with the distal HPV 18-speci®c AP-1 binding site provided identical results, indicating that there are no dierences in DNA anity and selectivity of the binding reaction (Ryseck and Bravo, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…26,27 HeLa cells were chosen as our EMSAs show that nuclear proteins derived from these cells produce the same binding pattern as those from HUVECs. In addition, Arts et al 9 have shown that t-PA gene expression is regulated in a similar fashion in HeLa cells as compared with HUVECs.…”
Section: The T-pa ؊7351c>t Polymorphism Affects Enhancer Responsivenementioning
confidence: 95%